Childrens Participation and Citizenship in a Global Age. Empowerment, Tokenism or Discriminatory Disciplining? - Hanne Warming (Social Work & Society, 2011)
This article explores children's participation and citizenship, taking its point of departure in the empirical observation of a paradox: On the hand there is a general participatory climate and a growing commitment to empowerment of children, and on the other hand some children's experience of discrimination, disciplining and distrust. The analysis is structured into three main parts: 1) Participation, approached from Hart's Ladder of Participation and Bourdieu's theorizing of power dynamics; 2) Rights, using Marshall's tripartite conceptualization, namely civil rights, political rights and social rights, supplemented by a discussion of the right to care and cultural rights; and 3) Identity, theorized using Delanty's conceptualization of citizenship as a learning process The article concludes that children's citizenship, and the initiatives that are accounted for as facilitating their well being and participation though social work, too often tend towards tokenism if not discriminatory disciplining and exclusion, rather than empowerment, due to political, organisational and discursively shaped power relations.